Plant species of popular use in pain management: a systematic review (Research, Society and Development, 2022)
Pain is an unpleasant sensory and emotional experience associated with actual or potential tissue damage; multifactorial in nature and recognized as a public health problem. Although with synthetic drugs used in therapy, increasing popular use of plants in the treatment and/or relief of pain has been observed; a situation that deserves to be highlighted as it allows selection of plant species for validation studies, but there are risks, as the use of plant-based inputs for therapeutic purposes requires certification of efficacy, safety and quality. Thus, this work aims to carry out a review of ethno-directed studies of plant species used in popular practices for pain treatment. The search was performed in the Scielo, LILACS and Pubmed databases, including articles published from 2011 to 2021, using the descriptors “pain”, “ethnobotany” and “phytotherapy”. 66 articles were selected, with a predominance of publications in Brazil and India, in English; with 70 plant species mentioned, belonging to 40 families, predominantly the Asteraceae family (12.35%). The most mentioned plant species were Curcuma longa L. (7.14%), Zingiber officinale Roscoe (5,71%) and Mentha x piperita L. (4,28%); predominating the use of leaves (54.54%), prepared by decoction (15.15%) and aqueous extraction (13.63%). Although several plant species are popularly used to treat pain, there are still few studies on safety and efficacy certification for therapeutic use. This review indicates species to be selected for continuation with a validation study, aiming to contribute to the offer of new treatment options for pain, but raises the need for Pharmacovigilance actions in Phytotherapy.